Documentary voice & vision a creative approach to non-fiction media production = Documentary voice and vision - Anderson, Kelly; Lucas, Martin; Hurbis-Cherrier, Mick (Focal Press, 2016)
This comprehensive work combines clear, up-to-date technical information, production techniques, and gear descriptions with an understanding of how technical choices can create meaning and serve a director's creative vision. Drawing on the authors' years of experience as documentary filmmakers, and on interviews with a range of working professionals in the field, the book offers concrete and thoughtful guidance through all stages of production, from finding and researching ideas to production, editing, and distribution. "Documentary Voice & Vision" will help students and aspiring filmmakers think through research and story structure, ethics, legal issues, and aesthetics, as well as techniques from camera handling to lighting, sound recording, and editing. The book explores a full range of production styles, from expository to impressionistic to observational, and provides an overview of contemporary distribution options.
Includes chapter notes with bibliographical references, glossary, filmography, and index. - Description based on print version record
Keywords: Documentary films -- Production and direction; Cinematography; Motion Pictures; Documentaires; Production et réalisation; Cinéma; PERFORMING ARTS / Film & Video / General; Documentary films; Production and direction